An Overview of e-Health in Indonesia: Past and Present Applications - Dwi Cahya Astriya Nugraha; Ismiarta Aknuranda (Institute of Advanced Engineering and Science, 2017)
Indonesia is the largest archipelagic country in the world. There are five major islands and thousands of smaller islands, most of which are in the distance. Therefore, its health services are hardly distributed. E-Health is one of the methods expected to deal with the problem of distance in health services. The development and use of technology in health area has given rise to several studies on the applications of e-Health in Indonesia. Based on a number of studies, we find that e-Health in Indonesia has been applied since 1985. The technologies and features used from time to time were growing in some period of time. However, the study also shows that from that point of time the number and variety of technologies and features provided are decreasing and the focus shifted to further analysis of the problems needed to be solved and provision of technologies and features only relevant to those problems. The development of e-Health applications in Indonesia has given promising results in providing health services, but they are still conducted by certain educational institutions and their uses are not evenly distributed throughout Indonesia.